AB0839 Evaluation of serum levels of N-terminal prob-type natriuretic peptide (NT-PROBNP) in patients with polymyositis and dermatomyositis (PM/DM): Preliminary data. (23rd January 2014) - Barsotti, S.; Neri, R.; Iacopetti, V.; d'Ascanio, A.; Tavoni, A.; Marta, M.; Pepe, P.; Carli, L.; Bombardieri, S.
Abstract : Background: symptomatic clinically cardiac involvement in PM/DM is rare but seems to be one of the most important cause of death 1 . High Nt-proBNP levels are commonly considered a marker of heart failure and were recently detected in rheumatic diseases without clinically evident heart involvement. Some authors hypothesize that high Nt-proBNP values can be likely considered indicators of subclinical cardiac damage 2 . Objectives: evaluation Nt-proBNP levels in a group of patients with PM/DM compared with normal healthy subjects. Methods: we enrolled consecutive PM/DM patients ( Bohan and Peter criteria) hospitalized in our Unit from 2006 to 2010; in all of them we measured Nt-proBNP serum levels (normal values <125 pg/ml) and performed an echocardiographic evaluation. We excluded patients with reduced left ventricular function (EF<55%), kidney failure, ischemic cardiomyopathy, arrhythmias and clinical history for other cardiovascular diseases. The most common cardiovascular risk factors as hypertension, hypercholesterolemia, diabetes, smoke were evaluated. Results: we enrolled 34 patients (21 PM and 13 DM); 26 female and 8 male, mean age 54 years [24-76]; mean disease duration 24 month [0-24], and a group of 32 healthy subjects, comparable for age and sex. Mean value of Nt-proBNP levels was 352 pg/ml in PM/DM patients (440 pg/ml in PM, 217 pg/ml in DM) and 51 pg/ml in control group ( p<0.001 ). We also subdivided PM/DM and the control group according to the presence of cardiovascular risk factors and compared Nt-proBNP levels in 4 groups. Data are reported in the table In PM/DM patients, the presence of cardiovascular risk factors increased widely Nt-proBNP levels (536 vs 103 pg/ml; p=0.006) while in the controls group the values were only lowly increased (60 vs. 41). In the subgroups without cardiovascular risk factors (2 and 4), Nt-proBNP mean values, even if in the normal range, were higher in PM/DM group than in healthy subjects ( p=0.074 ). In presence of cardiovascular risk factors, Nt-proBNP mean values were higher in the subgroup 1 compared with subgroup 3 ( p=0005). Conclusions: This data suggests that, even without evident cardiac involvement, in presence of cardiovascular risk factors, patients with PM/DM have higher Ntpro-BNP levels and probably an higher risk to develop heart involvement. This intriguing aspect needs to be studied in detail in a larger amount of patients and controls, to establish the weight of the single cardiovascular risk factor. References: Lundberg I: The heart in dermatomyositis and polymyositis. Rheumatology (Oxford) 2006; 45 Suppl 4: iv 18-21. Giannoni A, Tani C et al: When the heart is burning: amino-terminal pro-brain natriuretic peptide as an early marker of cardiac involvement in active autoimmune rheumatic disease. Int J Cardiol. 2011;148(2):161-7. Disclosure of Interest: None Declared